Las falencias que presente la ley penal ecuatoriana en los delitos sexuales en niños, niñas y adolescentes. Estudio de casos en la Fiscalía de delitos sexuales en la ciudad de Machala en el periodo 2011-2012 y propuesta de reforma a la ley penal del libro II capítulo III título VIII en los delitos sexuales en niños, niñas y adolescentes. - Badillo Alvarado, Rosa Otilia (2013)
The increase in sexual offenses is alarming, even more so when this kind of crime is committed in children and adolescents, as only leave irreparable consequences but often end up with the life of the victim is for this reason that we have seen in the need for a thorough study of this kind of crimes to determine whether the penalties established in our penal code book II Chapter III of title VIII of sexual offenses of children and adolescents, are really corrective or permissive. As we progress in our research and supported by surveys of the general public we have been able to conclude that an urgent change in our criminal law by the safety index is needed it is very high our children and adolescents are in constant danger of being sexually assaulted taking into account that the attackers are strangers to them not only individuals but can also be people known as teachers, neighbors, clergy, coaches and even family ancestors or descendants of the victim.